Keeping school children safe and alive : strategies to stop bullying and prevent suicide - Gillians, Phyllis E.; Cooper, Bruce S. (Emerald Publishing Limited : Information Age Publishing, Inc., 2021)
"To raise awareness of all members of the community - children, parents and school staff about the harm that bullying causes and how children & young people can be protected, including solutions to the problem of rising incidents of bullying and cyber bullying in connection with the use of social networks. This book will improve strategies and responses to incidences of bullying that will address the causes and effects of bullying and help avoid any recurrence. This book will provide assistance for the empowerment of all Administrators, school staff and parents as change agents in reducing bullying and in the education of children and young people in peer led strategies. Further cooperation between schools, local school administration and other outside agencies in the reduction of bullying"--